An Overview of Patients with ENT Disorders at Shalakya Outpatient Department, Ayurveda Teaching Hospital, Institute of Medicine, Tribhuvan University, Kirtipur - Sadhana Parajuli; Patel, Karunesh Singh; Mala Yadav; Gupta, Rupam Kumari (Journal of Ayurveda Campus, 2025)
Background: Ear, Nose, and Throat (ENT) diseases pose a significant public health challenge, affecting a large number of patients worldwide. The study was conducted to assess the prevalence of ear, nose, and throat (ENT) disorders among patients visiting at Shalakya Outpatient Department of Ayurveda hospital Kirtipur. Materials & Methods: It was an analytical retrospective study OPD data record of Shalakya Department in the fiscal year 2081-82 BS. Main focus was outpatient department and Ayurveda therapeutic treatment of Shalakya department in ENT diseases diagnosed patients only. All the patients who came with ENT problem were enrolled in the record of Shalakya OPD data of one year from 2081 Baishak- 2082 Baishak and those data were taken for the study. Results and Discussion: The majority of the patients 47.5% were from 21-40 year age group and mean age is 39.0 years. More patient visited to OPD were from Kathmandu 34.3%. The maximum number of 50.9% that is more than half of patient had case of nose problem, 25.0% of cases were related to ear diseases, while 14.4 % of cases were related to throat problems. The majority of the patients who presented with nose problem 159 (27.7%) were suffering from allergic rhinitis followed by rhinosinusitis 74 (12.9%). Most common ear problem was tinnitus 54 (9.4%) followed by otalgia and chronic suppurative otitis media both 4.2%. Ayurveda therapeutic applied to cure ENT diseases in Ayurveda Teaching Hospital like Nasya was advice in the maximum patients 63.3%, followed by Karnapuran in 19.9%. Conclusion: Total patient visited to Shalakya OPD were 573 and total diseases diagnosed was 623 because multiple diseases were found in single patients. Most common disease was Allergic rhinitis because Kathmandu is the most polluted city in Nepal so maximum people suffer by allergic Rhinitis.